Delayed therapy with clopidogrel and everolimus prevents progression of transplant arteriosclerosis and impairs humoral alloimmunity in murine aortic allografts - Heim, Christian; Eckl, Sebastian; Preidl, Raimund; Ramsperger-Gleixner, Martina; Koch, Nina; Goldmann, Katja; Spriewald, Bernd M.; Weyand, Michael; Ensminger, Stephan M. (European Journal of Cardio-Thoracic Surgery, 2015)
It was previously shown that the combination of clopidogrel and everolimus reduced the development of transplant arteriosclerosis. The aim of this study was to investigate whether delayed onset of treatment, similar to the clinical situation after heart transplantation, inhibits progression of transplant arteriosclerosis.Fully allogeneic C57BL/6 (H2-b) donor aortas were transplanted into CBA.J (H2-k) recipients treated with clopidogrel and everolimus alone or in combination starting on Days 1, 7 or 14. Grafts were analysed by histology and alloantibodies were detected by fluorescence activated cell sorting after transplantation.Delayed platelet inhibition with clopidogrel reduced the development of transplant arteriosclerosis [neointima formation (Day 14): 50 ± 4 vs 84 ± 9% (control)]. The combination of clopidogrel and everolimus almost abolished formation of transplant arteriosclerosis when therapy was started on Day 1 [neointima formation (Day 1): 14 ± 5 vs 84 ± 9% (control)] and also showed a remarkable reduction in both delayed treatment groups [neointima formation (Day 7): 24 ± 7 vs 84 ± 9% (control); neointima formation (Day 14): 28 ± 11 vs 84 ± 9% (control)]. Platelet inhibition alone and in combination with everolimus resulted in reduced alloantibody production.These results demonstrate that delayed treatment with clopidogrel and everolimus-representative of a clinical setting-prevents the progression of transplant arteriosclerosis and impairs humoral immunity in this experimental model.
EVALuna2:16087